2009
DOI: 10.1053/j.gastro.2009.06.002
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Recapitulating of TP53 Mutagenesis in Hepatocellular Carcinoma Associated With Dietary Aflatoxin B1 Exposure

Abstract: Background & Aims-Dietary exposure to aflatoxin B 1 (AFB 1 ), in addition to other known factors, increases risk for human hepatocellular carcinoma (HCC). HCCs from AFB 1 -exposed individuals frequently have distinct TP53 mutations, such as G to T transversions in the 2 nd guanine of codon 249 (AGG to AGT), and a characteristic mutational spectrum predominated by G:C to T:A mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 52 publications
4
68
0
Order By: Relevance
“…Accumulation of mutations without concomitant reduction in embryonic progeny survival indicates that sequencing provides a more sensitive genotoxicity assay than measuring reduced survival of progeny. The aflatoxin signature matches mutation profiles reported in the TP53 gene in human aflatoxin-induced hepatocellular carcinomas, namely, a preponderance of C>T transitions and C>A transversions (equivalently, G>A and G>T) occurring with a strand bias indicative of evidence of transcription-coupled nucleotide excision repair (Petitjean et al 2007;Besaratinia et al 2009). …”
Section: Resultssupporting
confidence: 66%
“…Accumulation of mutations without concomitant reduction in embryonic progeny survival indicates that sequencing provides a more sensitive genotoxicity assay than measuring reduced survival of progeny. The aflatoxin signature matches mutation profiles reported in the TP53 gene in human aflatoxin-induced hepatocellular carcinomas, namely, a preponderance of C>T transitions and C>A transversions (equivalently, G>A and G>T) occurring with a strand bias indicative of evidence of transcription-coupled nucleotide excision repair (Petitjean et al 2007;Besaratinia et al 2009). …”
Section: Resultssupporting
confidence: 66%
“…Recent evidence confirmed that this position is a preferential site for AFB1 adduct formation. 37 In Thailand, the main dietary sources of AFB1 are maize and groundnuts. Individual exposure to AFB1 has been estimated to range from 53 and 73 ng/kg/day, although this figure is likely to vary widely among different geographic areas and ecological zones.…”
Section: Role Of Aflatoxin Afb1mentioning
confidence: 99%
“…AFB1 is metabolized in the liver into an epoxide that covalently binds to the N7 position of guanine at the third base of codon 249 in the TP53 gene (AGG, encoding arginine), resulting in a transversion mutation which is extremely rare in cancers other than liver (AGT, encoding serine, R249S mutation, mutant protein p.R249S) (27,28). There is a strong ecological concordance between high exposure to AFB1 and a high proportion of R249S-positive HCC (up to 70z in parts of China and Africa).…”
Section: Molecular Mechanismsmentioning
confidence: 99%